In search of sustainable water management international lessons for the American West and beyond - Kenney, Douglas S., 1964-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2005)
Water issues in the American West share many similarities with those seen elsewhere in the world as population growth exacerbates longstanding problems of inappropriate water use and management. The contributors to this timely volume examine the universal challenge of sustainable water management to improve the use of water resources already developed and find ways to moderate our growing collective thirst.
Water policy and cultural exchange : transferring lessons from around the world to the western United States / James L. Wescoat Jr -- Roles for the public and private sectors in water allocation : lessons from around the world / Charles W. Howe and Helen Ingram -- Integrating environmental and other public values in water allocation and management decisions ; Protecting indigenous rights and interests in water / David H. Getches and Sarah B. Van de Wetering -- Transboundary water conflicts and cooperation / Aaron T. Wolf -- Sustainability and the future of western water law / Lakshman Guruswamy and A. Dan Tarlock.
Includes bibliographical references and index.
Keywords: Water-supply -- West (U.S.) -- Management; Water resources development -- West (U.S.); Sustainable development -- West (U.S.); Water-supply -- Management -- Case studies; Water resources development -- Case studies; Sustainable development -- Case studies; Electronic books